Africanos y afrodescendientes en Centroamérica: - Lowell Gudmundson (Nuevo mundo - Mundos Nuevos, 2009)
An analysis of novel forms of researching Afro-Central American history during the 19th and 20th centuries. Comments on the sources, strategies and results of recent studies that recover the history of African-descent populations traditionally identified with the mestizo or ladino majorities and not only those of the Atlantic coast commonly recognized as Afro-Americans.